2012
DOI: 10.2478/v10247-012-0049-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses of spring rape plants to soil flooding

Abstract: A b s t r a c t. Stress responses of spring rape to soil hypoxia were investigated during 8-days flooding. Soil air-filled porosity decreased from 25-30% to 0%, oxygen diffusion rate -from 2.6-3.5 to 0.34 µmol O 2 m -2 s -1, and redox potential -from 460 to 150 mV within few hours. Alcohol dehydrogenase activity in roots increased up to 7-fold after one day of flooding and then decreased to 170% of control. Superoxide dismutase activity in roots increased by 27% during first 3 days and then dropped to 60% of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Under drought conditions, soil moisture decreased up to 30 % and lower; under the full soil flooding, it increased up to 120 % of TWC by the volume (Kalashnikov et al 1994). The availability of oxygen to roots of plants changed under flooding during a few hours as following: E g decreased from 25-30 to 0 % (Balakhnina et al 2009); ODR in the root zone decreased from 120 to 6 μg m À2 s À1 (Zakrzhevsky et al 1995) or from 2.28-3.44 to 0.09-0.28 μmol O 2 m À2 s À1 ; Eh decreased from 543 to 70 mV (Balakhnina et al 2009(Balakhnina et al , 2012. The soil measurements performed during the period of drainage showed that the soil parameters in the flooded treatment variants returned to the control values already after 2 days of free drainage (Balakhnina et al 2010).…”
Section: Soil Water and Aeration Statusmentioning
confidence: 99%
“…Under drought conditions, soil moisture decreased up to 30 % and lower; under the full soil flooding, it increased up to 120 % of TWC by the volume (Kalashnikov et al 1994). The availability of oxygen to roots of plants changed under flooding during a few hours as following: E g decreased from 25-30 to 0 % (Balakhnina et al 2009); ODR in the root zone decreased from 120 to 6 μg m À2 s À1 (Zakrzhevsky et al 1995) or from 2.28-3.44 to 0.09-0.28 μmol O 2 m À2 s À1 ; Eh decreased from 543 to 70 mV (Balakhnina et al 2009(Balakhnina et al , 2012. The soil measurements performed during the period of drainage showed that the soil parameters in the flooded treatment variants returned to the control values already after 2 days of free drainage (Balakhnina et al 2010).…”
Section: Soil Water and Aeration Statusmentioning
confidence: 99%
“…Too compacted a soil loses its ability of infiltration and prevents rainwater storage, which causes fast water flow and soil erosion (Cudzik et al, 2010). Soil compaction caused by multiple tractor units passing through the farm fields can cause shallow rooting of the plants and changes in roots morphological features (Bartholomew and Williams, 2010;Głąb, 2013;2012a,b;Powałka, 2008), while oxygen deficit in the soil is a reason of plants growth suppression (Balakhnina et al, 2012). The intensity and kind of cultivation which affect soil structure have also a significant meaning for microbiological activity or organic compounds content in the soil (Blouin et al, 2008;Gajda and Przewłoka, 2012;Sławiński et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…oxygen and carbon dioxide in plants. The slow rate of gas diffusion in water limits the oxygen supply (Visser and Voesenek, 2004;Tan et al, 2010;Balakhnina et al, 2012). Soil flooding due to excess rains or seepage from large reservoirs may damage crops completely as it causes a dramatic impact on biochemical activities viz., aerobic respiration and photosynthesis in stagnant or slow-moving water (Armstrong and Drew, 2002;Islam et al, 2008;Jackson, 2008;Else et al, 2009).…”
Section: Introductionmentioning
confidence: 99%